The state of the art of bispecific antibodies for treating human malignancies. Issue 9 (24th August 2021) - Wang, Shuhang; Chen, Kun; Lei, Qi; Ma, Peiwen; Yuan, Andy Qingan; Zhao, Yong; Jiang, Youwei; Fang, Hong; Xing, Shujun; Fang, Yuan; Jiang, Ning; Miao, Huilei; et al.
Abstract: Bispecific antibodies (bsAb) that target two independent epitopes or antigens have been extensively explored in translational and clinical studies since they were first developed in the 1960s. Many bsAbs are being tested in clinical trials for treating a variety of diseases, mostly cancer. Here, we provide an overview of various types of bsAbs in clinical studies and discuss their targets, safety profiles, and efficacy. We also highlight the current challenges, potential solutions, and future directions of bsAb development for cancer treatment. Abstract : In this review, N. Li, Y. Nie & colleagues provide an overview of the current clinical development and future directions of bi‐specific antibodies for cancer treatment.